2023
DOI: 10.1002/anie.202216562
|View full text |Cite
|
Sign up to set email alerts
|

Superlattice‐based Plasmonic Catalysis: Concentrating Light at the Nanoscale to Drive Efficient Nitrogen‐to‐Ammonia Fixation at Ambient Conditions

Abstract: Plasmonic catalysis promises green ammonia synthesis but is limited by the need for co-catalysts and poor performances due to weak electromagnetic field enhancement. Here, we use two-dimensional plasmonic superlattices with dense electromagnetic hotspots to boost ambient nitrogen-to-ammonia photoconversion without needing co-catalyst. By organizing Ag octahedra into a square superlattice to concentrate light, the ammonia formation is enhanced by � 15-fold and 4-fold over hexagonal superlattice and disorganized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Lee group also demonstrated that the highly intense local electric field provided by the wellorganized Ag octahedra superlattice greatly boosts the adsorbed N 2 activation, reducing the energy barrier of N 2 reduction without extra cocatalyst. 59 This local electric field-assisted O 2 / N 2 activation was also theoretically verified by Montemore and co-workers on Au and Ag NPs in different electric field configurations. 60 In addition to O 2 dissociation and N 2 reduction, our group further declared the interesting role of the local electric field in CO 2 reduction.…”
Section: Local Electric Field Assistancesupporting
confidence: 66%
See 1 more Smart Citation
“…Lee group also demonstrated that the highly intense local electric field provided by the wellorganized Ag octahedra superlattice greatly boosts the adsorbed N 2 activation, reducing the energy barrier of N 2 reduction without extra cocatalyst. 59 This local electric field-assisted O 2 / N 2 activation was also theoretically verified by Montemore and co-workers on Au and Ag NPs in different electric field configurations. 60 In addition to O 2 dissociation and N 2 reduction, our group further declared the interesting role of the local electric field in CO 2 reduction.…”
Section: Local Electric Field Assistancesupporting
confidence: 66%
“…In this case, NN dissociation in a dissociative pathway under moderate conditions was achieved rather than in a common associative pathway. Lee group also demonstrated that the highly intense local electric field provided by the well-organized Ag octahedra superlattice greatly boosts the adsorbed N 2 activation, reducing the energy barrier of N 2 reduction without extra cocatalyst . This local electric field-assisted O 2 /N 2 activation was also theoretically verified by Montemore and co-workers on Au and Ag NPs in different electric field configurations …”
Section: Plasmon-mediated Selective Activationmentioning
confidence: 68%
“…We begin by synthesizing AgOcta with well-defined octahedron morphology and broad localized surface plasmonic resonances (LSPR) across the visible spectrum via the polyol reduction method (edge length, 404 ± 9 nm; Figure 1B; Figures S1, S2A, and S3A, Supporting Information). [7,26] Cu 2 O nanoparticles are subsequently grown on AgOcta via the in situ reduction of Cu(II) precursor. We direct the spatial deposition of Cu 2 O nanoparticles on either 1) the AgOcta's edges and vertices (edge-AgOcta@Cu 2 O) or 2) over the entire AgOcta surfaces (full-AgOcta@Cu 2 O) by exploiting the differences in surface energies between its vertices, edges, and faces.…”
Section: Resultsmentioning
confidence: 99%
“…[5] These light-matter interactions can also be easily tuned and enhanced by manipulating the structural features of plasmonic nanoparticles (e.g., size and shape) and/or organizing them in proximity to promote inter-particle plasmonic coupling, resulting in the modulation of plasmonic catalytic activities. [6][7][8][9] Upon light excitation, the plasmonic nanoparticles undergo localized surface plasmon resonance (LSPR) that amplifies the localized electromagnetic field near the metal surfaces. [10] Subsequent plasmon decay leads to the generation of energetic charge carriers (e.g., hot electrons and hot holes) for driving target reduction-oxidation (redox) reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in introducing light into heterogeneous catalytic reactions has mainly been driven by its potential to replace the fossil energy consumption with clean solar energy. On the one hand, light can decrease the activation energies of chemical conversion processes by relying on contributions from light-induced carriers, and it has been observed to be dominant in catalytic systems based on semiconductors and plasmonic metals. On the other hand, photothermal catalysis represents another important mechanism that converts the absorbed light energy into heat, resulting in a high localized temperature of the catalyst, which effectively enhances the catalytic reaction performance. …”
Section: Introductionmentioning
confidence: 99%